Highly Relevant Mentoring (HRM) as a Faculty Development Model for Web-Based Instruction / Highly Relevant Mentoring (HRM) (mentorat haute efficacité), un modèle de formation du corps professoral à l'enseignement en réseau - Lorraine Carter; Vincent Salyers; Aroha Page; Lynda Williams; Liz Albl; Clarence Hofsink (The Canadian Network for Innovation in Education (CNIE), 2012)
This paper describes a faculty development model called the highly relevant mentoring (HRM) model; the model includes a framework as well as some practical strategies for meeting the professional development needs of faculty who teach web-based courses. The paper further emphasizes the need for faculty and administrative buy-in for HRM and examines relevant theories that may be used to guide HRM in web-based teaching environments. Of note is that HRM was conceived by the instructional design staff who contributed to this paper before the concept of high impact mentoring appeared in the recent literature (2009). While the model is appropriate in various disciplines and professions, the examples and scenarios provided are drawn from a Canadian university's experience of using HRM, in conjunction with a pedagogical approach called ICARE, in a variety of nursing courses and programs. Cet article décrit un modèle de formation du personnel enseignant intitulé « highly relevant mentoring (HRM) » (mentorat haute efficacité); ce modèle comprend une structure et des stratégies pratiques visant à combler les besoins en formation du corps professoral d'une faculté offrant des cours en réseau. L'article souligne la nécessité d'un appui facultaire et administratif au HRM et étudie les théories pertinentes pouvant servir à guider le HRM dans des milieux d'enseignement en réseau. On notera que le HRM a été conçu par l'équipe de conception de matériel pédagogique qui a contribué à cet article avant l'apparition, dans les publications récentes (2009), du concept de « high impact mentoring » (mentorat à haut rendement). Bien que ce dernier modèle convienne à diverses disciplines et professions, les exemples et les scénarios fournis ici sont tirés de l'expérience d'utilisation du HRM dans une université canadienne, conjointement à une approche pédagogique appelée ICARE, dans une variété de cours et de programmes de sciences infirmières.